The impact of pitch values on image quality and radiation dose in an abdominal adult phantom using CT - Lança, Luís (2017)
Different parameters on CT can be used to reduce the patient radiation dose. One of these parameters is pitch, which is defined as the table movement per 360 degrees rotation time divided by the beam width. The use of a high pitch can reduce the radiation dose and the scan time. When the CT scan is acquired within a shorter time, possible motion artefacts can be reduced. This is useful when scanning areas in which there is a lot of involuntary movement, such as the cardiac and lung regions. However, it is important to consider the effect of a higher pitch on image quality, particularly on the spatial resolution. On the other hand, a low pitch might be chosen when high image quality is needed. Consideration has to be made when deciding whether the effective radiation dose counterbalances the image quality. This study aims to identify the impact of pitch on image quality and effective dose for axial and coronal planes in abdominal adult CT.